Increased sample entropy in atrial fibrillation relates to cardiac autonomic dysfunction determined by heart rate variability: A preliminary study - Rattapong Sungnoon (2018)
Introduction: Atrial fibrillation (AF) is the most common cardiac arrhythmia associated with an increased risk of left atrial thrombosis as well as ischemic stroke. In this study, we have evaluated the characteristics of paroxysmal AF (PAF) and persistent AF using sample entropy (SampEn), a new biosignal parameter for determining degree of AF signal complexity in atrial activities extracted from surface ECG, including heart rate variability (HRV) to test the hypothesis that increased atrial signal irregularity in AF patients relates to cardiac autonomic dysfunction compared with control subjects. Methods: PAF patients with normal sinus rhythm (n = 12), persistent AF patients (n = 11), and control subjects (patient controls; n = 8, and healthy controls; n = 13) were recruited. The ECG recordings (sampling rate of 1000 Hz, 5-minute long) were performed, then standard short-term HRV and SampEn were analyzed by software algorithms. Results: SampEn values from lead V1 in patients with persistent AF were significantly higher than those in healthy controls (0.14±0.02 vs. 0.10±0.04). Although there was no SampEn difference between PAF patients and the other three groups, the PAF SampEn was in between persistent AF and control values. For HRV analysis, low-frequency to high-frequency (LF/HF) power ratio in both PAF and persistent AF patients were significantly decreased compared to healthy controls (0.75±0.52 and 0.44±0.09 vs. 1.56±0.77, respectively). Conclusion: There was an impairment of cardiac autonomic function in both PAF (with normal sinus rhythm) and persistent AF patients consistent with an increased atrial signal irregularity. ©2012 IEEE.